MIS of the Hip and the Knee A Clinical Perspective - Scuderi, Giles R.; Tria, Alfred J. (Springer New York, 2004)
This is a new and exciting period in orthopedic surgery. Times are cha- ing,and we are developing techniques to perform joint arthroplasty through smaller and smaller incisions in an effort to reduce the amount of int- operative trauma and expedite the path to recovery. Minimally invasive surgery (MIS) leads to shorter hospital stays with quicker recoveries. The procedures may eventually be performed on an outpatient basis with an earlier return to daily activities and work. We have asked the leading world authorities in this ?eld of orthopaedics to contribute their ideas on these new techniques. Because so much of the technology is new, the authors cannot present signi?cant long-term foll- up. However, with their cooperation, we can present the most current knowledge about the ef?cacy of MIS. Thomas P. Sculco,Mark A. Hartzband, and Richard A. Berger have summarized their early experiences with m- imally invasive surgical total hip arthroplasty in a succinct manner. Paolo Aglietti, Jean-Noël A. Argenson, and David W. Murray have provided - depth impressions of the European experience with unicondylar knee arthroplasty. John A. Repicci, a pioneer in MIS knee surgery, presents his experience with unicondylar knee arthroplasty. Finally,Thomas M. Coon adds his own experience to give a glimpse into the future of MIS total knee arthroplasty. We are grateful to all of the authors and contributors to this text for their time and consideration. It is our hope that this work will be the foundation for the future of MIS total hip and knee arthroplasty.